Lévy Distribution Meta-Heuristic Fuzzy-Based Optimization Algorithm for Optimal Framework Design of Type-2 Fuzzy Controller: Subject to Perturbations - Himanshukumar Rajendrabhai Patel (Proceedings, 2024)
New metaheuristic algorithms have recently been created based on Lévy Flight (LF), drawing inspiration from biological and natural events [...]